Plugin JavaScript 100 POWER SOLUTIONS - Nixon (McGrawHill, 2012)
Filled with ready-to-use JavaScript solutions for creating dynamic web content, this practical guide is will save you hundreds of hours of programming time!  Plug-in JavaScript delivers 100 JavaScript power solutions in one handy guide.